ATTRACTION OF ARTHROPODS IN REFUGIA BLOCKS (Ageratum conyzoides L., Capsicum frustecens L., and Tagetes erecta L.) WITH THE APPLICATION OF LIQUID ORGANIC FERTILIZER AND BIOPESTICIDE IN APPLE CROPS IN PONCOKUSUMO - Tria Irma Muhibah; Amin Setyo Leksono (University of Brawijaya, 2015)
The objective of this research was to know the community structure of arthropods and to know visiting patterns of arthropods in refugia blocks. The method used in this research was Visual Encounter in fruiting season and flowering season. The observation was held four times in each season and four times a day. The observation was held on the refugia blocks that were applied a liquid organic fertilizer and biopesticide (POCB) and Control. Measurement of abiotic factors was done including temperature, humidity and light intensity. The result was analyzed using important value (INP) and Shannon-Wienner Index (HI). Overall the total abundance of arthropods was 32 family in flowering season and 33 family in fruiting season. All of the refugia blocks were dominated by family Muscidae in flowering season and dominated by family Apidae in fruiting season. The Diversity of arthropods in flowering season and fruiting season is quite high with the value was ranged from 3 to 4. Arthropods visiting patterns on the refugia block showed an increase in the abundance of arthropods in period 2 that was during 9:00 to 10:30 am. Key word : Arthropods, Biopesticide, Flowering Season, Fruiting Season, Liquid Organic Fertilizer, Refugia Blocks, Visual Encounter